Globalization and Trans-nationalism (American Journal of Islam and Society, 2006)
On 10 August 2006, The National Advisory Council for South Asian Affairs(NACSAA) met at the Cosmos Club in Washington, DC, to answer severalquestions: Do markets know best? Does the market really know? Are the richgetting richer and the poor getting poorer? Does globalization meanWesternization and/or Americanization? Are traditional societies being dissipated?As there were many speakers, I will present only brief summaries.Shabir Ahmed stated that the West uses its foreign aid to get countriesto follow its own standards and perspectives, while many members of theelites have abandoned the traditional lifestyle. On the positive side, globalizationsolves poverty through the market. Syed Akhtar asked whether globalizationwas the same as McDonaldization or Nikeification, or just aboutcultural domination and sweatshops. He sees globalization as a win-win situation,provided that a nation has the necessary “enabling conditions”: ahighly educated workforce, the rule of law, and democratic institutions.V. Balachandran reminded the audience that globalization also causesproblems. In India, this takes the form of increasing farmer suicides, shantytowns, a lack of investment in the agricultural sector, a decrease in the quality of life, and questions of who owns the country’s natural resources. JamesClad defined globalization in negative terms: It is not necessarily an acrossthe-board integration of economies, a generator of an immediately improvedsecurity environment, a trend of deepening skill sets and the development ofan industrial and an R&D culture, something new (it is a recurrent phenomenonenabled by technological advancement), or westernization, for all culturesborrow what is useful to them.Abdul Mommen claimed that the South Asian diaspora can help root outterrorism. Currently, South Asia is facing higher levels of terrorism; inAmerica and western Europe, these levels are actually declining or increasingonly marginally. Bangladesh, despite being a liberal Muslim state, is seeingits level of terrorism, as well as the number of fatalities, grow even fasterthan has been the case in the Middle East since 9/11. Vijay Sazawal spokeon self-governance and trans-nationalism in Kashmir. He pointed out thatwhile Pakistan calls for more self-rule in Indian Kashmir, it provides almostnone to its own Kashmiri citizens. He concluded that “the line of control(LOC) is more or less a pretty clean division between various ethnic entitiesthat make up the old princely state and that the current boundary can sustainregional stability even when its political future is questioned.” ...